Кон Collective, Gender and Excellence in the Making: Për Collective, Gender and Excellence in the Making - Ivanovska, Marija; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Marija Ivanovska | Марија Ивановска Title (Macedonian): Кон Collective, Gender and Excellence in the Making Title (Albanian): Për Collective, Gender and Excellence in the Making Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 239-240 Page Count: 2 Citation (Macedonian): Марија Ивановска, „Кон Collective, Gender and Excellence in the Making“, Идентитети: списание за политика, род и култура, т. 3, бр. 1 (лето 2004): 239-240. Citation (Albanian): Marija Ivanovska, „Për Collective, Gender and Excellence in the Making“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004): 239-240.